الوحدات العسكرية الرومانية في موريطانيا القيصرية "الكتائب والفصائل أنموذجا - توريرت, مصطفى (جامعة الوادي - University of Eloued, 2021)
The Roman Military body was adepted to and in accord with the growing expansion to the peoples of the Mediteranean basin, the joining of new provinces meant adding more Roman military forces which continnally needs new human sources, if the proconsulare and Numidia provinces were put under the protection of the third Augustan legion, the provinces Mauretania Caesarea and tingitane were only protected by the helping units, this military units were put under the authority of governor of the province, according to archeologicul documents (Military diplomates, tombstones, monuments) which were found in the region of Caesarea Mauretania in which those units settled or its solder were buried in, we were able to identify the names of the roman militry units and the origins of its soldiers and their military ranks and even the period of their coming and the missions they did. The units brought from the European and oriental regions represented the majority during the first century and the beginning of the second one, later they were replaced by the local military units starting from the middle of the second century A.D, with the existence of the factor of specializing in arms which demands requires the formation of permanent proups and Cohors from members who were skilful in using the required arm, this units were supported by additional temporary units whose presence was linked to the situation of Caesarea Mauretania or on its frontiers, this army had different roles military, economic, and civilizational, in addition to its guaranteeing the security of the province it contributed to the spread of the Roman culture arong the local peaple thorughe including the Maurs via military service which enabled them to get Roman Citizenship in iddition, it contributed to augmenting the military value of the Allied tribes which were close to the Province a their warrior.
مقال
Keywords: موريطانيا القيصرية,الجيش الروماني,الكتائب,الفصائل,الشهادات العسكرية; The Roman army ; Cohors ; Numerus ; Military diplomates ; The Roman army ; Cohors ; Numerus ; Military diplomates ; Mauretania Caesarea ; The Roman army ; Cohors ; Numerus ; Military diplomates ; Mauritania Caesarea ; The Roman army ; Cohors ; Numerus ; Military diplomates